Carnosinase activity of human gastrointestinal mucosa. Issue 8 (August 1975) - Sadikali, F; Darwish, R; Watson, W C
Abstract : Carnosinase, the dipeptidase which hydrolyses carnosine and other histidine-containing dipeptides, was assayed in mucosal tissues of the human and of the rat gut. Kinetic properties of the intestinal enzyme were found to be similar to carnosinase of other animal tissues. Little or no activity was detected in human gastric or colonic mucosa, and the levels were lower in duodenal than jejunal mucosa. The distribution of carnosinase is similar to that of the disaccharidases. Mean carnosinase activity was 8-8 units/g weight in 15 patients with histologically normal mucosa compared with 5-7 units in five with villous atrophy. The enzyme levels increased with histological improvement of the mucosa in patients with coeliac disease on a gluten-free diet. Tolerance curves for carnosine and its constitutent amino acids showed malabsorption of the dipeptide in a patient with carnosinase deficiency. It is concluded that the intestinal mucosa has much less hydrolase activity for carnosine than for glycylglycine and other dipeptidases, and the relatively slow hydrolysis appears to be the rate-limiting step in the total absorptive process.